Role of Corporate Social and Environmental Responsibilities in addressing Sustainable Development Goals: Evidence from Malaysian Manufacturing Firms - Abdurrahman, Adamu Pantamee; Mohamad, Shafi; Sibghatullah, Amena; Keong, Ooi Chee; Hieu, Vu Minh; Mutira, Putri (International Journal of Energy Economics and Policy, 2022)
Recently, sustainable development goals (SDGs) have been the requirement of every organization around the globe that requires researchers and regulators’ focus. Hence, the present study examines the impact of corporate social responsibilities (CSR) in addressing the SDGs of manufacturing companies in Malaysia. The current article also examines the mediating impact of organizational effectiveness among the linkage of CSR and SDGs achievement. The researchers have used the survey method and taken the questionnaires for data collection. The current article has also applied the smart-PLS to analyze the data collected from selected respondents. The results indicated that CSRs have a positive linkage with the SDG’s achievement. The findings also exposed that organizational effectiveness significantly mediates among the linkage of CSR and SDGs achievement in manufacturing companies of Malaysia. The article has guided the policymakers regarding developing the regulations related to the SDG’s achievement through CSR and organizational effectiveness.